2018
DOI: 10.3847/1538-4357/aaad68
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Evolution within an Erupting Coronal Cavity

Abstract: Coronal cavities have previously been observed associated with long-lived quiescent filaments and are thought to correspond to the associated magnetic flux rope. Although the standard flare model predicts a coronal cavity corresponding to the erupting flux rope, these have only been observed using broadband imaging data, restricting analysis to the planeof-sky. We present a unique set of spectroscopic observations of an active region filament seen erupting at the solar limb in the extreme ultraviolet (EUV). Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…we made the EOVSA images at one-quarter of the available resolution of 1 s). The initial rise of the ejecta and flux rope during the first 10 minutes, which were studied by Doschek et al (2018) and Long et al (2018), manifests as an upward-moving feature apparent in the AIA 193Å and 131Å data, outlined with black-dashed curves in Fig. 3a and 3b, respectively.…”
Section: Temporal Developmentmentioning
confidence: 91%
See 1 more Smart Citation
“…we made the EOVSA images at one-quarter of the available resolution of 1 s). The initial rise of the ejecta and flux rope during the first 10 minutes, which were studied by Doschek et al (2018) and Long et al (2018), manifests as an upward-moving feature apparent in the AIA 193Å and 131Å data, outlined with black-dashed curves in Fig. 3a and 3b, respectively.…”
Section: Temporal Developmentmentioning
confidence: 91%
“…The event has received considerable attention in the literature in the few months since it occurred (e.g. Warren et al 2018;Yan et al 2018;Li et al 2018;Long et al 2018;Omodei et al 2018;Doschek et al 2018). Figure 1 shows an overview of spatially-integrated lightcurves for emission at different wavelengths, and the total power microwave dynamic spectrum from EOVSA.…”
Section: Observationsmentioning
confidence: 99%
“…The launch of the extremely fast erupting MFR and CME likely drove a global shock ahead of it indicated by the extreme ultraviolet (EUV) waves (or EIT waves, Dere et al, ) in SUVI's 195 Å passband (Figure b and better shown in a movie in the online version of Seaton & Darnel, ). This strong EUV wave had a speed of at least 1,000 km/s and even up to 2,000 km/s, which places it among the fastest EUV waves observed (Long et al, ; Liu et al, ). It propagated across the entire solar disk within half an hour starting from the eruption at 15:53 (Seaton & Darnel, ).…”
Section: The Flare Cmes and Gle 72: Close To The Sunmentioning
confidence: 95%
“…Perhaps the brightest and longest-lived plasma-sheet observation to date is associated with an X8.2-class flare on September 10th 2017 (e.g. Long et al 2018;Warren et al 2018;Kuridze et al 2019;Li et al 2018, Cheng et al 2018Longcope et al 2018;Gary et al 2018;Morosan et al 2019). The flare and coronal mass ejection erupted from AR 12673 on the western solar limb, observed across the spectrum by multiple spacebased and ground-based instruments.…”
Section: The Plasma-sheet Associated With the September 10th 2017 Flarementioning
confidence: 99%